Characteristics of matrix structures and their effects on project success - Schnetler, Rohann; Steyn, Herman; Van Staden, Paul J. (South African Journal of Industrial Engineering, 2015)
This paper investigates the characteristics of matrix structures and their relationships with drivers of project success, such as communication, collaboration, and trust between project team members. Matrix characteristics that were expected to correlate positively with project success mostly did correlate with the success drivers. However, characteristics expected to impact negatively on project success did not show such significant correlations; some even correlated positively with success drivers. The success drivers investigated, in turn, correlated positively with perceived project success. A proposed model illustrates the effects of matrix characteristics on the drivers of success and their ultimate effect on project performance.